A study on the morphometric asymmetry of atlas vertebrae - Mohd Salahuddin Ansari; S, Mukesh; KB, Binaya; C, Nilotpal (Faculty of Medicine, UKM Medical Centre, 2016)
The commonly used examination procedures of the upper cervical spine depend upon the symmetry for comparison and interpretation of joint functions. If symmetry is not normal, then these assessments may mislead the examiners, allowing them implementation of incorrect treatment plans. Objectives of this study are to explore the possibility that asymmetry is more common than symmetry and, if it is true, to find out the effects of asymmetry on the biomechanics of these joints. The study was carried out on 30 atlas vertebrae of cadavers of Indian origin. The different intra-atlas distances were measured on both sides by digital vernier calliper. All the parameters studied showed statistically significant differences between the right and left side i.e. a p value of < 0.05. The antero-posterior diameter of the foramen transversarium, the transverse diameter of the foramen transversarium, the distance from the midline to medial edge of the vertebral artery groove (inner as well as outer cortex) and the length of the superior articular facets were more on the right side as compared to the left side. The breadth as well as the length of the inferior articular facet, the breadth of the superior articular facet and the difference of posterior arch thickness at the site of vertebral artery groove were more on the left side as compared to the right side. These differences may be explained by the handedness of an individual, which influences the intra-osteal asymmetry in a characteristically distinct manner, which needs to be confirmed or refuted in a further study.